How the COVID-19 pandemic impacted the dental trauma urgence attendance in a public reference hospital: A retrospective study (Research, Society and Development, 2024)
The objective of the work was to verify whether there is a difference in the standards of care and the incidence of dental trauma cases in a public reference hospital, before and during the COVID-19 pandemic. A retrospective cross-sectional study of dental records was carried out in the urgency and emergency service of the Municipal Hospital Odilon Behrens, part of the Unified Health System (SUS), from March to December of the years 2019 and 2020. To compare the standards of care, a descriptive analysis, Pearson's chi-square test and Fisher's exact test, with a significance level of 95%. A 52% reduction in care was observed during the pandemic, with statistically significant changes (p